Proteomic analysis of human substantia nigra identifies novel candidates involved in Parkinson's disease pathogenesis. Issue 6 (18th February 2014) - Licker, Virginie; Turck, Natacha; Kövari, Enikö; Burkhardt, Karim; Côte, Mélanie; Surini‐Demiri, Maria; Lobrinus, Johannes A.; Sanchez, Jean‐Charles; Burkhard, Pierre R.
Abstract : Parkinson's disease (PD) pathology spreads throughout the brain following a region‐specific process predominantly affecting the substantia nigra (SN) pars compacta. SN exhibits a progressive loss of dopaminergic neurons responsible for the major cardinal motor symptoms, along with the occurrence of Lewy bodies in the surviving neurons. To gain new insights into the underlying pathogenic mechanisms in PD, we studied postmortem nigral tissues dissected from pathologically confirmed PD cases ( n = 5) and neurologically intact controls ( n = 8). Using a high‐throughput shotgun proteomic strategy, we simultaneously identified 1795 proteins with concomitant quantitative data. To date, this represents the most extensive catalog of nigral proteins. Of them, 204 proteins displayed significant expression level changes in PD patients versus controls. These were involved in novel or known pathogenic processes including mitochondrial dysfunction, oxidative stress, or cytoskeleton impairment. We further characterized four candidates that might be relevant to PD pathogenesis. We confirmed the differential expression of ferritin‐L and seipin by Western blot and demonstrated the neuronal localization of gamma glutamyl hydrolase and nebulette by immunohistochemistry. Our preliminary findings suggest a role for nebulette overexpression in PD neurodegeneration, through mechanisms that may involve cytoskeleton dynamics disruption. All MS data have been deposited in the ProteomeXchange with identifier PXD000427 (http://proteomecentral.proteomexchange.org/dataset/PXD000427 ).